Sámi communities in Sweden and Norway and the reappropriation of the past : a comparative study of the return of the skeletal remains in Rounala and Neiden - Martin-Wurtz, Laura (Helsingin yliopisto, 2022)
The rise of the scientific theories and race biology at the beginning of the 20th century was one of the main factors that caused the Sámi people to be marginalized, as they were characterized as “inferior” for the rest of the Nordic citizens. They were photographed, measured, and the remains of their ancestors were exhumated and taken to universities to serve as material and evidence for the racial theories of the time. The purpose of this thesis is to study and emphasised the arguments used during the discussions about the repatriations of the human remains in both cases to understand the outcomes and the impacts on the Sámi societies. To understand the development of both process and their outcomes, a comparative analysis of different medias covering the subjects at this time was done, following the ideas of Asgeir Svestad and Kjell-Åke Aronsson, in order to synthetize the information and reach a conclusion. Since the 1970’s, Sámi peoples have been fighting for their rights and self-determination in multiple fronts, notably by demanding the repatriation of the remains of their ancestors to their lands. The Rounala case in Sweden and the Neiden case in Norway are two examples of repatriation among the Sámi communities. Both were covered by the medias and rised numerous discussions about the handling of the human remains as part of cultural heritage in the context of colonialism. Different opinions were expressed about the potential reburial of the remains and the possibilities further to analyse the bones to learn more about the Sámi history. The development of the cases led to the reburial of the human remains from Neiden and the remains from Rounala to be archived in the Ájtte museum in Jokkmokk for several years.